Posouzení vybraných ukazatelů podniku pomocí analýzy časových řad - Kraus, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalářské práce obsahuje analýzu obchodní společnosti KÁMEN-DEKOR, s.r.o. s užitím časových řad, regresní analýzy a ekonomických ukazatelů. Práce je rozdělena na teoretickou a praktickou část, ve které budeme analyzovat vybraná data. Závěrečnou část práce tvoří návrhy na zlepšení ekonomické situace v podniku.

My Bachelor work includes analysis of the business company KÁMEN-DEKOR, s.r.o. with application of the time series, regression analysis and economic indicators. Work is divided into theoretical and practical part, in which we will be conduct the analysis of the selected figures. Final part of work includes the improvement proposals of the economic situation in company.
Assessing Selected Indicators of a Company Using Time Series Analysis
Keywords: Časové řady; finanční ukazatele; regresní analýza; statistická data.; Time series; financial indicators; regression analysis; statistic data.